Social interactions and status markers in the Roman world - Cupcea, George; Cupcea, George; Varga, Rada; Varga, Rada (Archaeopress Roman archaeology, 2018)
Proceedings from the 'People of the Ancient World' conference held in Cluj-Napoca, Romania in 2016. 10 papers encompass diverse approaches to Roman provincial populations and the corresponding case-studies highlight the multi-faceted character of Roman society